Alliances with universities - how firms absorb and apply knowledge. (2015) - Santoro, Michael D.; Gopalakrishnan, Shanthi
Expanding on the notion that absorptive capacity is a multi-dimensional construct, we elaborate on a pivotal component of absorptive capacity, applying external knowledge (AEK), by examining the extent to which certain key internal and external factors are related to AEK. Using survey questionnaire data from senior executives in firms collaborating with university research centres our focus was AEK with respect to advancing new products, new processes, and improvements to existing products and processes. Results show that a more technologically uncertain environment is positively associated with AEK and the firm age is associated with AEK in a curvilinear, inverted U-shape fashion such that as firms mature they apply external knowledge better up to a certain point until diminishing returns come into play. We also found tacit knowledge and explicit knowledge moderate these relationships in different ways. We conclude with implications for future theory development, empirical research, and management practice.